Analysis Productivity Chemical Industry in Indonesia - Effendi, Amanda Lailatul Khofifah; Restikasari, Wenny (MediaTrend, 2025)
This research aims to determine Technical Efficiency Change (TEC), Scale Efficiency Change (SEC), Technological Change (TC), Total Factor Productivity (TFP) in the chemical industry in Indonesia. Using data form large anda medium manufacturing industries in Indonesia, the Stohastic Frontier method is used to determine TEC, SEC, TC, TFP. The results of the average TEC, SEC, TC, TFP show negative changes for productivity in the chemical industry in Indonesia. Based on the research results, the company must provide incentives in the form of subsidies or financial assistance to replace old machines with more efficient technology and maintain the stability of raw material prices.